Peran Tokoh Adat Dalam Penyelesaian Kasus Kekerasan Terhadap Perempuan Di Desa Saukibe, Kecamatan Amfoang Barat Laut - Manit, Charlens Elmaden; Medan, Karolus Kopong; Kian, Darius Antonius (Artemis Law Journal, 2023)
Victims of violence against women even occur every day in Sukibe Village, North West Amfoang District. Cases of violence have become a crucial problem and require hard efforts to improve it by all parties. One example of violence that occurs is violence against women or domestic violence (domestic violence). ) for the period 1 January 2022 to 31 December 2022, 1 case was recorded that was successfully mediated. The problem formulation in the research is (1) How do traditional leaders act in efforts to resolve cases of violence against women in Saskibe Village, North West Amfoang District? (2) What are the obstacles in the process of imposing customary sanctions in Saukibe Village, North West Amfoang District? This research method uses empirical research methods, meaning that analyzing problems is carried out by combining data obtained in the field. The results of the research show, 1) the role of traditional leaders in efforts to resolve cases of violence against women, namely bringing together the perpetrators and victims of the family in mediation and present traditional leaders 2) Obstacles in the process of imposing customary sanctions. Pelaky gives all kinds of reasons and does not want to be responsible for the sanctions given, but as a traditional leader will try to make the perpetrator responsible for his actions. Resolving cases of violence against women in Saukibe Village, District. North West Amfoung, aleko sfd nok ha ook bak (repairing the relationship between the perpetrator and the victim and the two extended families) It is recommended to the amof and traditional leaders that the Aafant taleko tradition in the role of providing assistance in cases of violence against women to continue to preserve the traditional pillai and also introduce tradition in the younger generation